Formulasi Sediaan Krim Body Scrub Kombinasi Ekstrak Daun Kemangi (Ocimum sanctum L.) dan Beras Putih (Oryza sativa L.) - Yunita Yunita; Nanang Yunarto; Firdha Senja Maelaningsih (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2021)
Premature aging is one of the most common skin problems caused by free radicals. Basil leaves (Ocimum sanctum L.) contain flavonoid compounds that function as natural antioxidants to ward off free radicals. Rice (Oryza sativa L.) is rich in protein, carbohydrates, fats, pigments, minerals, as well as vitamins B6, B12, B1, and vitamin E. Body scrub cream is a skin care cosmetic product that is widely used. This study aims to obtain a physically stable body scrub cream formulation from a combination of basil leaf extract and white rice. The cream was made of oil in water (W/W) type by emulsification method with 3 variations of formula and basil leaves were extracted by maceration method. The results showed that in the third 4 weeks of the formula, there was no change based on the results of the organoleptic test, homogeneity test, pH, spreadability, and viscosity. From this study it was found that the combination of basil leaf extract and white rice can be formulated in body scrub preparations with formula I the most stable combination of 3% basil leaf extract and 10% rice.